Chest pain: a review of current principles and approaches to first aid - A. A. Birkun; L. I. Dezhurny (Российский кардиологический журнал, 2022)
Chest pain is a typical manifestation of acute myocardial ischemia. The likelihood of death in myocardial infarction increases significantly as the pain to hospital times increase, Therefore, timely recognition of this symptom as a possible manifestation of ischemia, calling an ambulance and first aid before the arrival of ambulance team can play a vital role in saving lives. A review of modern principles and rules for first aid to patients with chest pain is presented, based on an analysis of international and national guidelines. We demonstrated the need and identified directions for improving the organization of first aid in this condition in Russia, as well as analyzed approaches to remote questioning and provision of instructions on first aid for chest pain by ambulance dispatchers by phone, Based on the comparative analysis of dispatcher guidelines and protocols and international guidelines on first aid for chest pain, a universal Russian-language dispatcher algorithm for remote care for chest pain has been developed, which is proposed for discussion and further testing as a potential component of a unified domestic dispatcher support program for first aid.